Investigating Port Spatiality: Tools for a Spatial Approach to Port Clusters - Beatrice Moretti (Ocean and Society)
Today, half of European port managing bodies administer two or more ports. Contemporary port‐city territories are increasingly shaped by processes of “spatial clustering,” which call for a reassessment of the tools used to investigate and design these areas. Port clusterization refers to the administrative aggregation of two or more ports into clusters, a phenomenon that has the potential to affect port spatiality by defining a new spatial typology of ports, characterized by polycentricity and territorial extension. Despite the absence of established theories and tools for analysing such extended spaces, the rise of port clusters is giving way to new governance models for optimizing coastal areas and specializing land–sea infrastructures. This article, part of the EU‐funded PULSE (The Port‐clUster LandScapE) project, examines the impacts of port clusterization by introducing the concept of “port‐cluster landscapes”—whose investigation contributes to developing a spatial and design‐based approach to ports. In this context, the port‐cluster landscape emerges as a spatial typology of interconnected ports and overlapping flow systems. Methodologically, the article outlines the tools formulated to study two Italian port clusters, including multi‐level maps and the Indicator System, a set of 12 spatial indicators conceived within the framework of the project and being applied to these cases. Ultimately, the article explores port spatiality, highlighting the need for new regional collaborations and spatial reconceptualization, which can be fostered through transformative design projects in the context of port clusterization.